2010
DOI: 10.1155/2011/546560
|View full text |Cite
|
Sign up to set email alerts
|

Black Tea and Theaflavins Assist Healing of Indomethacin‐Induced Gastric Ulceration in Mice by Antioxidative Action

Abstract: The healing activities of black tea (BT) and the theaflavins (TF) against the indomethacin-induced stomach ulceration were studied in a mouse model. Indomethacin (18 mg/kg, p.o.) administration induced maximum ulceration in the glandular portion of the gastric mucosa on the 3rd day, accompanied by increased lipid peroxidation and protein oxidation, depletion of thiol-defense and mucin, as well as reduced expressions of cyclooxygenases (COX) and prostaglandin (PG) E synthesis in the gastric tissues, and plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 49 publications
8
51
0
Order By: Relevance
“…Moreover, [19] suggested that, NSAIDs-induced impairment of the tight junction complex morphology and permeability between viable gastric mucosal epithelial cells may be a major contributing factor in the etiology of stomach disorder. The zymogenic granules of chief cell has a central deeper part with pale periphery, this was similar to the results of [20].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, [19] suggested that, NSAIDs-induced impairment of the tight junction complex morphology and permeability between viable gastric mucosal epithelial cells may be a major contributing factor in the etiology of stomach disorder. The zymogenic granules of chief cell has a central deeper part with pale periphery, this was similar to the results of [20].…”
Section: Discussionsupporting
confidence: 87%
“…TF healed indomethacin induced gastric ulcer by its antioxidative properties, synthesis of PGE2 and enhancement of mucin secretion. TF also helps to suppress various inflammatory modulators in ulcer margin [53]. eNOS modulation may be another possible pathway of gastric ulcer healing by TF [53].…”
Section: Camellia Sinensismentioning
confidence: 99%
“…TF also helps to suppress various inflammatory modulators in ulcer margin [53]. eNOS modulation may be another possible pathway of gastric ulcer healing by TF [53].…”
Section: Camellia Sinensismentioning
confidence: 99%
“…PGs stimulate the secretion of bicarbonates and mucus, promote ulcer healing and inhibit the secretion of gastric acid. PGE 2 , one of the major PGs of the gastric mucosa, can inhibit the secretion of gastric acid (41). The ethanol-induced depletion of gastric mucus has been described previously (42), and this may be caused by an inhibitory effect on the gastric production of PGE 2 (43).…”
Section: Discussionmentioning
confidence: 95%